Perceptions of language teaching in science from student and teacher discourse - Garraway, James Windsor (Rhodes University, Faculty of Education, Department of Education, 1994)
The research was concerned with perceptions of language and physics in three strata of participants in a writing across the curriculum teaching course at an intermediate college. The participants were: a language teacher, two physics teachers and a class of twenty physics students - the students were studying in order to enter the Engineering Faculty at the University of Cape Town. The predominant understanding of the teachers was that of a limited interpenetration between the discourse of physics and language teaching. Physics teachers thought that language teachers would experience difficulties with both the concepts and language of physics. In actual practice however, students and the language teacher managed physics knowledge with some degree of success in the language classroom. Some students understood writing as helping them to understand physics. However, the dominant understanding of language was that of knowing the appropriate language of physics for their teachers. An appropriate language understanding was seen as potentially problematic in that it could encourage an unquestioning or monodimensional approach to physics knowledge. As a way around this problem, it was suggested that language teachers teach students to recognise and to use particular genres within science, and to develop their voice within these constraints.
Keywords: Physics -- Study and teaching -- South Africa; Language arts -- South Africa; Written communication -- Study and teaching -- South Africa; Language arts -- Correlation with content subjects -- South Africa; Physics teachers -- Language